Succession rules and leadership rents - Kai A. Konrad; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2005)
Leaders compensate supporters not just for performing their duties but also in order to preempt an overthrow by the same supporters. We show how succession rules affect the power of leaders relative to supporters as well as the resources expended on possible succession struggles. We compare two regimes of leadership succession: the conclave regime and the divide-et-impera regime which differ with respect to the role of supporters of the previous leader once the new leader takes power. The leadership rent is higher and supporters receive a lower compensation in the divide-et-impera regime, as supporters have to fight harder for succession to avoid the grim outcome of loss. A leader, then, would like to induce the divide-et-impera regime even when every supporter has veto power over his leadership.
Keywords: D74; D72; N40; H50; 330; political leadership; political support; political survival; successorship; Politiker; Regierungswechsel; Ökonomische Theorie der Demokratie; Rent Seeking; Theorie